(untitled) (European Journal of Education, 2020)
The main focus of the study was to explore the involvement of stakeholders in promoting the wellness of juvenile offenders in South African correctional schools. Two teachers and three juveniles were purposefully selected to complete open ended questionnaires from two juvenile centres in the Western Cape province of South Africa. The major aim of the study was to identify how different stakeholders can facilitate the attainment of wellness among juvenile offenders. The ubuntu and wellness theories were used as lenses to carry out the study. Research ethic procedures were followed. In order to get livid experience of participants, qualitative method was used to collect and analyse data. Findings revealed that stakeholder involvement varied with some being more involved while others were lacking. This compromised effective rehabilitation. It was recommended that the involvement of stakeholders should be intensified in order to have a greater impact on the rehabilitation of juvenile offenders.